O futuro do Direito - Fernandez, Atahualpa (Nómadas. Critical Journal of Social and Juridical Science, 2010)
This article discusses some issues about the impact that naturalistic perspectives have to do with the current theoretical and methodological structure of juridical science. A philosophy or science of law developed from a naturalistic approach allows to be opposed, a real and practicable form, to the evidence that human nature not only generates and limits the conditions of possibility of our societies but guides and sets limits to the institutional and normative set that regulates the social relations. To understand better our evolutionary past could provide the basis for a viable system with sense, for a Law to provide order and purpose to our lives in the future.
Keywords: Law; Evolution; Human nature; Juridical discourse; Legal education